COVID-19 Pandemic Impact on Cardiometabolic Markers in Adults in Chongqing, China: A Retrospective Cohort Study - He, Zhongxiang; Zhang, Yong; Xu, XiaoYang; Mei, Ying; Rahmani, Jamal; Seraj, Shaikh Sanjid; Qi, XiaoYa (Frontiers in Public Health, 2022)
COVID-19 infection and government-enforced lockdowns and social isolation changed people's lifestyles. Concerns regarding the health impact of the COVID-19 pandemic due to the new sedentary lifestyle. This study aims to investigate the impact of COVID-19 pandemic on cardiovascular health factors. A retrospective observational study was conducted using historical medical records. The cohort consisted of healthy adults (without chronic non-communicable diseases) over 18 years of age who have undertaken a health examination at the Chongqing Medical University from 2019 to 2020. The ANCOVA test was used to compare variables between 2019 and 2020. The effect of exposure time to COVID-19 on cardiometabolic markers was analyzed using multiple linear regression models. 29,773 participants took part in this study. Average age was 42.50±13.44 years at baseline, and the average follow-up period was 12.7±2.8 months. Analysis showed that weight, BMI, waist circumference, hip circumference, WHR, fasting blood glucose, TG, LDL, uric acid, and liver enzymes increased significantly during COVID-19 pandemic (P<0.05). This study showed evidence that the COVID-19 pandemic and its control measures negatively impacted cardiometabolic profiles.